Simplified method for quantifying the hydraulic properties of shrinking soils. Issue 1 (12th January 2015) - Schindler, Uwe; Doerner, José; Mueller, Lothar
Abstract: In general, soils and their pore size systems are assumed to be rigid during the loss of water on drying. In reality, it is not the case for most soils, especially for soils with high quantities of clay or organic matter. As a result of shrinking, there are changes in the bulk density, the porosity, the pore size distribution, and the hydraulic properties of these soils. Currently, only a few methods enable the shrinkage behavior of soil samples to be determined while simultaneously quantifying the corresponding soil hydraulic properties. Either the methods need proprietary software for data processing, the equipment used is expensive or the calculation of the hydraulic properties is executed by inverse modelling. The aim of this study was to develop an alternative, simplified method for the simultaneous and automatic determination of the soil hydraulic properties, taking shrinkage into account. The HYPROP® evaporative device was combined with a circumference meter. A preliminary investigation found that the diameter of the cylindrical samples used for the HYPROP decreased linearly during evaporation from the bottom to the top. To sum up, recording the perimeter change in the middle position of the sample during drying‐out, together with the corresponding tension and water content, was sufficient to determine the hydraulic functions taking shrinkage into account. Measurements are presented for 6 samples which are different in texture and geological origin. The maximum shrinkage (19.5% by vol. between saturation and 5, 000 hPa) was measured in the peat samples. The minimum shrinkage was quantified at 0.68% by vol. for the silty loam samples from Chile. The advantages of the method presented are: (1) the water retention curve and the hydraulic conductivity function can be determined simultaneously in the range between saturation and close to the wilting point, at a high resolution and taking into consideration shrinkage; (2) the method and device are simple and robust to use; (3) little time is required for measurement, between 3 and at most 10 d; (4) the functions are described over the whole tension range, using more than 100 user‐defined data points; (5) the evaluation of the volumetric soil water content measurement in shrinking soils is improved; and (6) common data models can be fitted to the hydraulic data as well as to the shrinkage data.